148k views
4 votes
Help! Pls I cant solve it help me with explanation also pls.

Help! Pls I cant solve it help me with explanation also pls.-example-1
User Quadfinity
by
4.9k points

1 Answer

4 votes

Given:

The expression is


(2)/(a-2)-(8)/(a^2-4)

To find:

The simplified form of the given expression.

Solution:

We have,


(2)/(a-2)-(8)/(a^2-4)

It can be written as


=(2)/(a-2)-(8)/(a^2-2^2)


=(2)/(a-2)-(8)/((a-2)(a+2))
[\because a^2-b^2=(a-b)(a+b)]

Taking LCM, we get


=(2(a+2)-8)/((a-2)(a+2))


=(2a+4-8)/((a-2)(a+2))


=(2a-4)/((a-2)(a+2))


=(2(a-2))/((a-2)(a+2))

Cancel out the common factors.


=(2)/(a+2)

Therefore, the simplified form of the given expression is
(2)/(a+2).

User Cyebukayire
by
5.3k points